INTERFACE CIRCUIT DESIGN USING DATA.LOG 4 CHANNEL - Yenny Wijayanti; Drs. Lingga Hermanto. MMSi (Jurnal Sistem Komputer, 2000)
At this writing, will discuss about the logging. Logging is the recording of different events work. Logging is the screen in graphical form (a function of time). Graph the results longging is a record / proof of a process. Given longging expected computer will not lose the data or information. Because the computer knows different longging facilitate incoming information at any time. Users only need to see the results of logging that is stored by the computer, making it easier job.